Numerical study on the effect of box and polygon geometry in fin and tube heat exchanger on fluid flow and heat transfer - Nugroho, Agung; Safi'i, Muhammad; Romadhon, Bukhori Putra; Wahid, Muhammad Abdul; Pujianto, Muhammad Edi (Politeknik Negeri Lhokseumawe, 2024)
Currently, fin and tube heat exchangers are widely used in various engineering applications, including modern heat exchangers, automotive radiators, and Air Conditioning (AC) systems such as evaporators, and condensers. Enhancing their performance necessitates innovative designs, advanced application, and optimizes geometries to improve heat transfer efficiency. This study investigates the effect of box and polygon geometries on fluid flow and heat transfer in a split Air Conditioner (AC) fin and tube heat exchanger using simulation software. The research examines two tube arrangement-inline and staggered-across different fluid velocities (0.5 m/s, 1 m/s, 1.5 m/s, and 2.5 m/s) and heat flux values (100 W/m2 , 125 W/m2, 125 W/m2, and 150 W/m2 ). The numerical study revealed that the best thermal and hydraulic performance of the fin and tube heat exchanger, based on geometry variations between box and polygon tubes, was achieved with the polygon tube geometry, which resulted in a lower temperature around 23.41°C. This temperature confirmed an increase in heat transfer coefficient by approximately 5% and Nusselt number by about 3%. The best performance overall, considering both thermal and hydraulic aspects, was observed in the inline arrangement, especially for the polygon tube, which resulted in a lower temperature of around 26.38°C. This confirmed an improvement in the heat transfer coefficient by about 4% and the Nusselt number by 2.5%.